The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1nj05316g
|View full text |Cite
|
Sign up to set email alerts
|

A series of POM compounds constructed using a flexible ligand containing three coordination groups: electrocatalytic and photocatalytic reduction and amperometric detection of Cr(vi)

Abstract: Four polyoxometalate-based compounds were synthesized by hydrothermal method, namely [Ni2(HPtpi)(H2O)7.5Mo0.17(TeMo6O24)]·2.5H2O (1),[Co(HPtpi)2(H2Ptpi)2(GeMo12O40)2]·4H2O (2) and {[M(Ptpi)(H2Ptpi)(H2O)][(γ-Mo8O26)0.5(α-Mo8O26)0.5]}·4H2O (M = Co in 3; Ni in 4) (Ptpi = 1-[2-(3-Pyridin-4-yl-[1,2,4]triazol-4-yl)-propyl]-imidazol). Compound 1 exhibits a 3D...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…With the scan rate of 200 mV·s –1 , the mean peak potentials E 1/2 = ( E pa + E pc )/2 are +201 and +74 mV for I–I′ and II–II′, respectively. These two peaks are attributed to two consecutive two-electron processes of γ-Mo 8 anions . With changing the scan rates from 20 to 500 mV·s –1 , the cathodic and anodic peak potentials shift toward the negative and positive direction, respectively, with increasing scan rates.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…With the scan rate of 200 mV·s –1 , the mean peak potentials E 1/2 = ( E pa + E pc )/2 are +201 and +74 mV for I–I′ and II–II′, respectively. These two peaks are attributed to two consecutive two-electron processes of γ-Mo 8 anions . With changing the scan rates from 20 to 500 mV·s –1 , the cathodic and anodic peak potentials shift toward the negative and positive direction, respectively, with increasing scan rates.…”
Section: Resultsmentioning
confidence: 94%
“…These two peaks are attributed to two consecutive two-electron processes of γ-Mo 8 anions. 34 With changing the scan rates from 20 to 500 mV•s −1 , the cathodic and anodic peak potentials shift toward the negative and positive direction, respectively, with increasing scan rates. The redox current has a nearly linear growth along with increasing scan rate, indicating that the rate of electronic and ionic transport and the kinetics of interfacial faradic redox reactions are rapid enough.…”
Section: Synthesis Of [(Hmentioning
confidence: 96%
“…Anderson-type POM-MOFs have also attracted increasing interest. [112][113][114][115][116][117][118][119] In 2016, Wang et al 19a). 116 Furthermore, this material can serve as an electrocatalyst and used for electrocatalytic reduction of NO2 -, Cr(VI) and BrO3as well as the electrocatalytic oxidation of ascorbic acid.…”
Section: Anderson-type Pom-mofsmentioning
confidence: 99%
“…[112][113][114][115][116][117][118][119] In 2016, Wang et al 19a). 116 Furthermore, this material can serve as an electrocatalyst and used for electrocatalytic reduction of NO2 -, Cr(VI) and BrO3as well as the electrocatalytic oxidation of ascorbic acid. 116 Besides, her group also introduced the multifunctional 3-(…”
Section: Anderson-type Pom-mofsmentioning
confidence: 99%
“…[15] The studies showed that various neurological problems such as Parkinson's disease, schizophrenia, some behavioral problems, Alzheimer's disease, and mental retardation occur due to excess lead in the body. [16] Because of the high toxicity of heavy metals on the ecosystem, many studies are currently being conducted on the determination [17][18][19] and removal of these metals by using different voltammetric techniques [20][21][22]. Also, traditional analytical methods such as atomic absorption spectroscopy [23], uorescence spectrometry [24], and atomic emission spectroscopy [25], can be used for this purpose.…”
Section: Introductionmentioning
confidence: 99%